Characterizing equipment on the heads of therapeutic/adaptive riding horses in the United States: a mixed-methods study of instructor decisions and practices - Reega, Sarah Jean, author; Peters, Brittany Caitlin, advisor; Matlock, Sarah, advisor; Butler, Sharon, committee member; Engle, Terry, committee member; Stallones, Lorann, committee member (Colorado State University. Libraries, 2025)
Therapeutic riding (TR) involves horseback riding lessons adapted for individuals with a wide range of disabilities. The TR horse is often ridden by the rider while being led by a horse leader. This ridden-while-led horse phenomenon is atypical compared to the rest of the equestrian industry, and it requires the unique application of equipment on the head of the horse. Further, this configuration lends itself to the opportunity for simultaneous conflicting pressure on the head of the horse from the rider's reins and from the leader's lead rope. Both equipment use and conflicting pressure have been shown to impact equine behavior, learning, and wellbeing outcomes. At present, there is no regulation or standardization of equipment on the ridden-while-led TR horse. For these reasons, there is a need to better understand how equipment is used in this setting, and why decisions are made about such equipment. Therefore, the aims of this research were to identify who makes decisions about the equipment on the head of the ridden-while-led horse, characterize the types of equipment used, and explore the important factors in TR instructors' decision-making process about such equipment. A two-part online survey was distributed to certified TR instructors in the United States via email listserv and social media, resulting in 403 (part 1) and 217 (part 2) complete responses. Descriptive statistics were calculated (1 and 2), and open responses were category coded (1) and analyzed using qualitative content analysis (2). In part 1, 86.10% of respondents self-identified as equipment decision-makers. The most commonly used equipment included bitted bridles (75.93%), traditional halters (75.19%), and sidepull bitless bridles (54.59%). Respondents used halters alone (65.91%), under bridles (43.75%), or over bridles (11.08%). Lead ropes were typically attached to the halter's bottom ring (75.94%) or a tie ring under the noseband (23.81%). Reins were attached to halter side buckles (60.05%), bits (56.66%), bitless bridle rings (53.79%), or halter jowl rings (31.59%). Most respondents (76.32%) felt that conflicting pressure occurred between rider and leader at least sometimes. Notably, many commonly reported equipment practices deviated from standard designs or broader industry norms. Further research is needed to explore the impact of these unconventional approaches, and how they may relate to conflicting pressure on the horse's head. In part 2, when presented with a list of decision-making factors, respondents most often considered riders' independence of the aids, the horse's temperament, and conflicting pressure to be important/very important factors in equipment decision-making (86.17%; 81.57%; 74.07%). Three themes emerged from the open-ended responses: who decisions concerned (horse, rider, and horse-human team), what they addressed (safety, equipment logistics, and the surrounding environment), and how individuals approached decisions (via observing and evaluating horse and rider, considering individuality, starting with as little equipment as necessary, collaborating, and relying on knowledge and experience). These data reflect multifaceted, complex, and individualized decision-making processes. Thus, there is a need for further research to guide such complex decisions.
Keywords: equipment; horse; welfare; equitation science; equine-assisted services; tack